Ambulatory Blood Pressure Monitoring–Derived Short‐Term Blood Pressure Variability in Primary Aldosteronism. Issue 8 (16th April 2015) - Grillo, Andrea; Bernardi, Stella; Rebellato, Andrea; Fabris, Bruno; Bardelli, Moreno; Burrello, Jacopo; Rabbia, Franco; Veglio, Franco; Fallo, Francesco; Carretta, Renzo
<x xml:space="preserve">Abstract</x> The aim of this study was to investigate the short‐term blood pressure (BP) variability (BPV) derived from ambulatory blood pressure monitoring (ABPM) in patients with primary aldosteronism (PA), either idiopathic hyperaldosteronism (IHA) or aldosterone‐producing adenoma (APA), in comparison with patients with essential hypertension (EH) and normotensive (NT) controls. Thirty patients with PA (16 with IHA and 14 with APA), 30 patients with EH, and 30 NT controls, matched for sex, age, body mass index, and antihypertensive therapy, were studied. The standard deviation (SD) of 24‐hour, daytime, and nighttime BP; 24‐hour weighted SD of BP; and 24‐hour BP average real variability were not different between patients with PA and those with EH (P=not significant). All BPV indices were higher in patients with PA, either IHA or APA subtypes, and patients with EH, compared with NT controls (P<.001 to P<.05). ABPM‐derived short‐term BPV is increased in patients with PA, and it may represent an additional cardiovascular risk factor in this disease. The role of aldosterone excess in BPV has to be clarified.